Royal Society of New Zealand’s Hutton Medal awarded to Professor Wendy Nelson - Editors (New Zealand Science Review, 2016)
​Professor Wendy Nelson MNZM FRSNZ, Pro-gramme Leader for Marine Biological Re-sources at NIWA and Professor at the School of Biological Sciences at the University of Auckland, has been awarded the Hutton Medal by the Royal Society of New Zealand for significantly expanding the knowledge of New Zealand’s seaweeds, also known as marine macroalgae. In a career spanning 35 years, she has discovered and documented the diversity of New Zealand flora throughout the region, from Te Rangitahua/Kermadec Islands to the Subantarctic Islands, and conducted research on taxonomy, evolution, algal ecology, alien seaweeds, and seaweed aquaculture and commercial harvesting. Her work on the ancient lineage of Bangiales, a type of red algae that includes Japanese nori seaweed, has resulted in New Zealand being recognised as a centre of diversity, requiring a reinterpretation of evolutionary relationships between world species. Over the past decade her research has focussed on the ecological importance of coralline algae, a calcified group of red algae, which form key habitats for a wide range of coastal organisms and are critical to the settlement and development of species such as pāua, but are vulnerable to climate change. She has also campaigned hard to get the most aggressive weeds eliminated from our coastal waters. In 2013 she published a popular guide to New Zealand seaweeds, making her extensive knowledge accessible to others1.In 2015 she chaired a major review by the Royal Society of New Zealand on biosystematics and taxonomic collections2. On being awarded the Hutton Medal, Professor Nelson said she had had the very good fortune to work with exceptional colleagues throughout her career. Moreover, she felt that New Zealand is an extraordinary place to work as a marine botanist with such diverse marine systems to study. ‘Our long isolation from other land masses and dynamic geological history have all contributed to the evolution of a rich and intriguing marine flora, and there is still a great deal to be discovered.’ Macroalgae are critical to the health and well-being of coastal ecosystems – and it is import-ant to discover and document our flora, understand how coastal systems function – in order to be stewards of coastal environments for future generations.’